Pengaruh Kemandirian Dan Orientasi Masa Depan Terhadap Motivasi Berprestasi Siswa Di SMK Negeri 1 Surakarta - Hizkia Greeny Delpbel Oktobrian; Cicilia Dyah Sulistyaningrum Indrawati; Susantiningrum Susantiningrum (Politeknik Kampar, 2024)
This research aims to (1) find out whether there is an influence of independence on students' achievement motivation; (2) find out whether there is an influence of future orientation on achievement motivation; (3) find out whether there is an influence of independence and future orientation on achievement motivation. The research uses a quantitative approach with descriptive correlational methods.. The population in this study were all students in class XII Office Management Automation, totaling 87 students, spread across 44 students in class A and 43 students in class B. Determining the sample size in this study used the Slovin formula with a sample size of 71 students. The research sample was taken using a proportional probability sampling technique with a proportion of class A totaling 36 students and class B totaling 35 students. The primary data collection technique in this research comes from answers to questionnaires. This questionnaire method is arranged according to a Likert scale with positive to negative gradations. Secondary data collection techniques in this research come from data sources that are not directly collected by researchers through libraries, documentation, books, scientific journals, written archives relating to the object under study. The data analysis technique uses the help of the IBM SPSS version 26 program. The research results show that (1) there is a significant positive influence of the independence variable on achievement motivation. This is proven by the significance value of 0.046 < 0.05 and the value of tcount > ttable (2.028 > 1.995); (2) there is a significant positive influence of the future orientation variable on achievement motivation. This is proven by the significance value of 0.002 < 0.05 and the value of tcount > ttable (3204 > 1.995); (3) there is a significant positive influence of the independence variable on achievement motivation. This is proven by the F test with a significance of 0.007 < 0.05 and a value of fcount > ftable (5.376 > 3.13). Based on the research results, it shows that the variables of independence and future orientation separately or jointly influence the achievement motivation variable..